Is There a Tradeoff Between Policy Responsiveness and Government Effectiveness? Evidence From the American States. Issue 2 (March 2023) - Flavin, Patrick
Citizens in a democracy expect elected officials will be responsive to their political opinions and govern in an effective way that improves their quality of life. However, a government that is too responsive to public sentiments may, in practice, be unable to govern effectively and promote societal well-being. This study is the first attempt to date to empirically evaluate this important potential tradeoff. Using newly developed measures of public opinion and public policy liberalism in the American states over time and a diverse battery of societal outcomes as well as multiple estimation strategies and timeframes, I find a weak and directionally inconsistent statistical relationship between policy responsiveness and government effectiveness. These findings have significant normative and theoretical implications because they suggest there is not a tradeoff between a government responding to its citizens' opinions and it governing effectively by promoting citizens' well-being.